“Z” Plasty Repair for Torn Ear Lobule - S. C. Lodha (Indian Journal of Plastic Surgery)
Due to the heavy earrings, the ear lobule is often torn in Indian women. The recurrence rate is high in commonly performed operations. “Z” Plasty operation in its treatment is devoid of recurrence and adds length to the shrunken ear lobules. This is the only operation which solves all the problems faced by a Surgeon.